Office XP brief - A Tutorial to Accompany Peter Norton's Introduction to Computers + CD - Norton Peter (American : McGraw-Hill, 2002)
Peter Norton's Office XP Brief is a stand-alone tutorial that features a strong instructional design. Small blocks of concepts followed by hands on activities and numerous full-screen illustrations result in clear-cut, easy-to-read instruction, making learning easy for students!
Product Description
Keywords: Công nghệ thông tin; Office XP; Tin học--Phần mềm